Slipped epiphyses in renal osteodystrophy. Issue 7 (July 1975) - Mehls, O; Ritz, E; Krempien, B; Gilli, G; Link, K; Willich, E; Schärer, K
Abstract : Clinical, biochemical, roentgenological, and histological features of slipped epiphyses (epiphysiolysis) in 11 out of 112 children with renal osteodystrophy have been analysed. Characteristic age-related patterns of involvement of different epiphyses are described. Quantitative measurements of iliac bone histology, serum parathyroid hormone levels, and clinical history show the presence of more advanced osteitis fibrosa in children with epiphysiolysis than in those without. A good correlation was found between serum parathormone levels and osteoclastic resorption, endosteal fibrosis as well as osteoid. Histological studies show that the radiolucent zone between the epiphyseal ossification centre and the metaphysis in x-rays is not caused by accumulation of cartilage and chondro-osteoid (as usually found in vitamin D deficiency rickets) but by the accumulation of woven bone and/or fibrous tissue. The response to vitamin D therapy in most cases was good. Parathyroidectomy was required in only one case.